Chasing the light: Positive bias in camera-based surveys of groundfish examined as risk-foraging trade-offs. (March 2019) - Frid, Alejandro; McGreer, Madeleine; Frid, Twyla
Abstract: Unbiased survey data are important for understanding the effects of fisheries and environmental change on fish communities. We applied predation risk and life history theories to examine how parallel laser beams, which provide a scale for estimating transect width and the sizes of fish and habitat features, might bias groundfish counts during visual surveys conducted with a towed video camera. The laser beams project forward as "dots" onto the benthos, and species differ in their propensity to chase them. We hypothesized that fish perceive the laser dots as potential food and the camera, which lags behind the dots while moving forward, as a generalized threat. Analyses accounted for species primary diet and tested the prediction that shorter-lived species are more likely to chase the laser dots than longer-lived species, but these differences should weaken in the perceived safety of larger groups. Consistent with our predictions, the probability that fish would chase the laser dots decreased with the maximum age of species and increased with group size, although these effects were independent of each other. Also, chase probabilities were ≈20 to 25 times greater for species known to include benthic mobile prey in their diet than for species that feed primarily on pelagic, sessile or low-mobility prey. Our results suggest that risk-foraging trade-offs are inherent to fish behaviors that might bias surveys counts. While further insight into species differences is still needed, we illustrate how group size- and species-specific chase probabilities can generate bias correction factors to improve surveys counts. Highlights: We examined fish behaviours that may bias survey counts conducted with a towed-video camera and parallel laser beams used as distance scalers. We hypothesized that fish perceive laser dots projected on the benthos as potential prey, and the moving camera as a generalized threat. Consistent with predictions, larger groups and shorter-lived species that feed on benthic mobile prey were more likely to chase the laser dots. We illustrate how group size- and species-specific chase probabilities can generate bias correction factors to improve surveys counts.